Contribution of radiobiphosphonates bone scan in multifocal tuberculous osteomyelitis - Nabih, Salah; Sahel, Omar; Benameur, Yassir; Doudouh, Abderrahim (World Journal of Nuclear Medicine, 2020)
We share the case of a 86-year-old male patient, followed up for recent left hip pain. Interrogation revealed a fever, nocturnal shivering, and bone pains. Standard radiographs and computed tomography centered on both shoulders and pelvis showed osteoarthritis of the left hip and multiple lytic lesions in both humeral heads and clavicles, suggestive of chronic infectious, metabolic, or secondary disease. Bone scan with radiobiphosphonates showed intense and diffuse uptake in the clavicles, the two humeral heads, and at the cervical and dorsal spine. Biopsy of the left humeral head confirmed the diagnosis of tuberculous osteomyelitis, showing an aspect of caseo-follicular tuberculosis. Bone scan with radiobiphosphonates can be used in our context to search other localizations falling within the framework of a polystotic form, and also to guide nonrisk biopsy in such group of patients.
Keywords: Bone scan; multifocal osteomyelitis; tuberculous osteomyelitis